2002
DOI: 10.1203/01.pdr.0000022343.57970.cf
|View full text |Cite
|
Sign up to set email alerts
|

Maturity of the Adrenal Cortex in Very Preterm Infants Is Related to Gestational Age

Abstract: To study the maturity of the adrenal cortex in preterms born before 33 wk of gestation, basal levels of cortisol and cortisone and the cortisol and 17-hydroxyprogesterone (17-OHP) response to 1 g/kg adrenocorticotropic hormone stimulation were measured in 24 appropriate-for-gestational age preterm infants (26-33 wk; 690-1985 g). Gestational age influenced the response of cortisol, 17-OHP, and the ratio between cortisol/17-OHP in the studied infants. In preterms born Ͻ30 wk of gestation, levels of cortisol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Instead, we found that preterm infants showed lower cortisol levels than full-term infants. Clinical studies have found that preterm neonates, while hospitalized in intensive medical care, may be at risk of adrenal insufficiency (e.g., Bolt et al, 2002). Accordingly, our findings suggest that a hyposecretion pattern of cortisol may persist in preterm infants up to 3 months of age (adjusted for gestation) especially those most exposed to neonatal pain (Granau et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we found that preterm infants showed lower cortisol levels than full-term infants. Clinical studies have found that preterm neonates, while hospitalized in intensive medical care, may be at risk of adrenal insufficiency (e.g., Bolt et al, 2002). Accordingly, our findings suggest that a hyposecretion pattern of cortisol may persist in preterm infants up to 3 months of age (adjusted for gestation) especially those most exposed to neonatal pain (Granau et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The larger (compared to fetal) placental contribution to F inactivation, however, is removed at birth. While plasma E levels do remain higher than at other times in life in both preterm and term infants [32,33,34], functional deactivation of F does not appear to occur after birth in infants born <30 weeks’ gestation, resulting in F levels higher than E [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…The ratios of cortisol/17-OH-progesterone and cortisol/cortisone were calculated to estimate the activities of 21a-hydroxylase and/or 11b-hydroxylase, and 11b-hydroxysteroid dehydrogenase (11b-HSD), respectively. 17…”
Section: Subjectsmentioning
confidence: 99%
“…The maturity of adrenocortical function is related to the duration of gestation, 17 but the timing of fetal adrenal involution in preterm infants is uncertain. 18,19 Thus, we hypothesized that maturity of the adrenal cortex in preterm infants is related to postmenstrual age, and that those with late-onset AOP have limited function to produce cortisol until the corresponding age of late gestation, 32e36 weeks postmenstrual age.…”
Section: Introductionmentioning
confidence: 99%